TheWorkQueue with Dynamic Replication-FaultTolerant Scheduler in Desktop Grid Environment - Bansal, Jyoti; Rani, Dr. Shaveta; Singh, Dr. Paramjit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Desktop Grid is different from Grid in terms of the characteristics of resources as well as types of sharing. Particularly, resource providers in Desktop Grid are volatile, heterogeneous, faulty, and malicious. These distinct features make it difficult for a scheduler to allocate tasks. Moreover, they deteriorate reliability of computation and performance. Availability metrics can forecast unavailability & can provide schedulers with information about reliability which helps them to make better scheduling decision when combined them with information about speed. This paper using these metrics for deciding when to replicate jobs & how much to replicate. In particular our metrics forecast the probability that a job will complete uninterrupted & our schedulers replicate those jobs that are least likely to do so. Our policy outperforms other replication policies as measured by improved Total CPU Time & reduced Waiting Time & Failure count